Nasyid music training for teenagers mosque in hamlet III pondok pasar 4 Damuli Kebun village Kualuh Selatan Labuhanbatu North Sumatra - Gulo, Hubari; Br. Perangin-angin, Alemina; Harahap, Agus Salim (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Indonesia has many cultures, almost every region has a different culture and customs. Labuhanbatu Utara is one of the regions in North Sumatra that has 8 districts. In South Kualuh sub-district has a habit to sing nasyid on certain and special events. Nasyid is one of the Islamic arts in the field of sound art. Usually it is a song that has an Islamic style and contains words of advice, stories of the prophets, praising God, and the like. Nasyid is usually sung in a cappella accompanied by only a drum. Community service program in 2019 is real community empowerment with the title Nasyid musyik training for mosque youth in Dusun III Pondok Pasar IV, Damuli Kebun Village, to provide useful knowledge for mosque youth.